Injury statistics and trends of ATP players - Spreen, D. (2001)
Since 1990, the ATP has been compiling player injury and illness statistics by looking at on-site medical withdrawals and retirements. An on-site medical withdrawal occurs when a player pulls out at some point after a tournament has begun. A retirement occurs when a player starts a match, but is unable to complete it. Data collected from all ATP Tournaments and the four Grand Slam Tournaments during the 2000 tennis season revealed that there were 106 on-site medical withdrawals, representing about 3.7% of total matches played during the year. There were 73 retirements during that same period, which accounted for 2.1% of all matches played. These numbers have shown incremental increases over the past 5 years and bear watching closely. What is important about this data is that it seems to contradict exaggerated reports in the press that injuries to tennis players are increasing at an alarming rate. Quite possibly one factor in the incremental increase is non-medical. There is a growing concern that a substantial percentage of on-site withdrawals from tournaments may be non-medical, even though an injury is used as an excuse to pull out of the tournament. While speculative, this effect is being watched and studied carefully this year, to see if our statistics are indeed skewed by non-medical factors. The ATP has also tracked the same injuries according to surface. In 2000, there were 38 withdrawals on hard courts, 30 on clay, 10 on grass, and 8 on indoor carpet. These numbers correlate very closely to the number of matches played on each surface. This number has stayed consistent over time, with no one surface showing more injuries per matches played than another or an increasing trend over time. For the total number of withdrawals and retirements, we have broken down player injuries by body part. In 2000, low back injuries accounted for 20 withdrawals. Foot and ankle injuries ranked second, accounting for 17 withdrawals, and hip and thigh injuries third, accounting for 15 withdrawals. Interestingly, shoulder injuries only accounted for six medical withdrawals.